'Just because one has attended a special class does not mean that one isn't capable': the experiences of becoming and being not involved in traditional occupations for young people with intellectual disability. Issue 4 (1st October 2020) - Luthra, Renee; Westberg, Niklas; Högdin, Sara; Tideman, Magnus
ABSTRACT: Young adults with intellectual disability face challenges in securing post-secondary school occupations. This can result in being Not in Employment, Education, or Daily activity (NEED). This qualitative interview study analyzes the subjective experiences of the process to becoming and being NEED. The analysis focuses on individual as well as structural factors, and how these are experienced in different arenas in society and in interactions with agencies. Interviews with 10 participants followed by thematic analysis were conducted. The results indicate that the process from secondary school to being outside of traditional occupations is not linear. Individual factors such as desires, abilities, and health problems, combined with structural factors of limited or unsuitable post-school occupations and challenges with formal support contribute to understanding people with intellectual disability who are NEED. The experiences of being NEED relate to social exclusion underlined with notions of normality and stigmatization of having an intellectual disability.